Additional English Language Materials and the Learners with Disabilities’ Learning Outcomes in Malaysia: A Correlational Study - Basaruddin, Muhammad Azwan; Mustafa, Hema Rosheny (Asian Journal of Assessment in Teaching and Learning, 2024)
This study explores the relationship between the use of additional instructional materials—including technological tools, pedagogical resources, and supplementary learning aids—by special education teachers and the classroom performance of learners with disabilities in Malaysia, as measured by Pentaksiran Bilik Darjah (PBD) assessments. The sample consisted of 33 special education teachers (22 females and 11 male), representing diverse teaching backgrounds and experience levels across Malaysian primary schools. Quantitative data were collected through teacher questionnaires and analysed using Spearman’s rank-order correlation and chi-square tests in SPSS 20.0. The findings revealed a strong positive correlation (r = 0.757, p < 0.001) between the frequency of additional material use and learners’ performance outcomes. Furthermore, a moderate correlation (r = 0.287, p < 0.01) was identified between teachers’ perceptions of learners’ performance and their reported use of additional materials. These results highlight the practical significance of incorporating structured and consistent additional materials to enhance learning outcomes for students with disabilities. The study underscores the need for standardising supplementary resources to ensure equitable access and effectiveness. Policymakers and educators are encouraged to develop guidelines for integrating these materials, emphasizing their role in promoting inclusive education practices and improving learner performance.